The Role of Ownership Concentration and Dividend Policy on Firm Performance: Evidence from an Emerging Market of Pakistan - Sadia Murtaza; Ahmad Noor-Ud-Din; Amel Aguir; Saadia Batool (SEISENSE Journal of Management, 2020)
Purpose- The main aim of this study is to determine the role of ownership concentration and dividend policy on the firm performance of chemical sector firms of Pakistan. Design/Methodology- This research used the secondary data collected from the annual reports of the companies listed at the Karachi Stock Exchange (KSE). However, inclusion criteria are the 26 listed firms from 2012 to 2017, giving a total of 156 observations. This study used the Generalized Least Squares Model. Findings- The findings reveal that ownership concentration has a significant positive association with firm financial performance. This stated that larger shareholders could attribute to the alignment of managerial incentives with shareholder interests. They also monitor the team very effectively and efficiently. The dividend policy has a significant positive relationship with ROA. Leverage and tangibility have a significant negative relationship with firm performance. Practical Implications- These results potentially can be relevant for policymakers and academic research as well as also helpful for managers and policymakers.